PERANAN SIKAP SKEPTIS AUDITOR DAN PENAKSIRAN RISIKO KECURANGAN DALAM MENDETEKSI KECURANGAN - Suzy Noviyanti (Jurnal Universitas Paramadina, 2013)
AbstractThe purpose of this research is to examine the efect of skeptical attitude and fraud risk assessment on auditors’ professional skepticism behavior of fraud detection. Experimental design is used in this research. The subject of this experiment consist of junior auditors, and senior auditor who work in public accounting firms in Central Java. ANOVA was conducted in this study to analysis the variance of auditor’s professional skepticism behavior between groups of auditors.There are some results in this research. First, skepticism attitude, and fraud risk assessment, influence the behavior of auditors' professional skepticism of fraud detection. Second, a motivation from the auditor’s supervisor such as a high assessment of fraud risk has an important role to maintain and improve auditors’ professional skepticism behavior particularly for auditors who have weak skepticism attitude. This results are supported the theory of attitudes – behavior relation described by Fazio (1990) in the MODE model (Motivation and Opportunity as DEterminants of the attitude-behavior relation) which states that when people are sufficiently motivated to do so, they can construct their attitude toward an object in an effortful manner. When motivation is low, only strong attitude – being chronically accessible – are likely to influence behavior (Fazio, 1990; Fazio and Towles-Schwen, 1999).Keywords: fraud risk assessments, auditor’s professional skepticism, fraud detection.